If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3h + 2c + f = 19 Reorder the terms: 2c + f + 3h = 19 Solving 2c + f + 3h = 19 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1f' to each side of the equation. 2c + f + -1f + 3h = 19 + -1f Combine like terms: f + -1f = 0 2c + 0 + 3h = 19 + -1f 2c + 3h = 19 + -1f Add '-3h' to each side of the equation. 2c + 3h + -3h = 19 + -1f + -3h Combine like terms: 3h + -3h = 0 2c + 0 = 19 + -1f + -3h 2c = 19 + -1f + -3h Divide each side by '2'. c = 9.5 + -0.5f + -1.5h Simplifying c = 9.5 + -0.5f + -1.5h
| -3(2x+4)=24 | | -4(x-2)+x=-4 | | 5x+3-2x=3x+10 | | 348.16+16.96+11.01=y | | 9=-9-2x | | 3x(x+2)(x+4)= | | 51=-3x | | -4x-42=-10 | | 3ex-4+8=10 | | -3(4-2x)+4x=x-21 | | 5(w+3)-(4w+5)=5 | | 7(r-5)(4r-1)=0 | | 66.64+7.42+11.01=y | | 38y+15y+22y+6y+44y+5y= | | 0x=76 | | -11+3x=-(2x-3)-4 | | -9x+76=-32-3x | | 2X*(2X+2)=624 | | 10x^4+19x^3+7X^2=0 | | -18x-6(-0.5)=-33 | | -16+x=5(2-5x) | | -x^4-x^2+6=0 | | -3X^2+24X-9=0 | | 6x^2-3x-84=0 | | (4x-3)-6=31 | | -4x-2y=30 | | 15-3(2m-4)=9 | | 5n-12=2(-n+1) | | 5n^3-31n^2+30n=0 | | 66.64+7.42+8.6=y | | 0.2x^2+3.7x-1.9=0 | | h=-16t^2+80t+44 |